2022
DOI: 10.3390/en15020465
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Olive Oil Industry along the Entire Production Chain and Related Waste Management

Abstract: The production of olive oil involves the sustainable management of the waste produced along the entire production chain. This review examines the developments regarding cultivation techniques, production technologies, and waste management, highlighting the goals to be achieved and the most reasonable prospects. The results show that cultivation and production technology have evolved to an almost final solution to meet economic feasibility, keeping the oil’s high quality. Continuous horizontal decanters will co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 137 publications
0
23
0
Order By: Relevance
“…Moreover, intensive drying of the pomace is required for extraction, increasing costs and uncertainty when it depends on fossil fuels. Overall, this could be related to the fact that olive pomace oil extraction plants have been dismissed in some countries, while in other countries like the USA this industry has not emerged [13]. Nevertheless, some industries use the dry and exhausted olive pomace (also called de-oiled and defatted olive pomace) obtained in the extraction process as a fuel resource to increase profitability.…”
Section: Extraction Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, intensive drying of the pomace is required for extraction, increasing costs and uncertainty when it depends on fossil fuels. Overall, this could be related to the fact that olive pomace oil extraction plants have been dismissed in some countries, while in other countries like the USA this industry has not emerged [13]. Nevertheless, some industries use the dry and exhausted olive pomace (also called de-oiled and defatted olive pomace) obtained in the extraction process as a fuel resource to increase profitability.…”
Section: Extraction Systemsmentioning
confidence: 99%
“…The olive oil extraction system will strongly influence the proportion and chemical composition of the biomasses generated, including the moisture, oil, and lignocellulose content [11][12][13]. This fact is crucial to establish management and valor-ization strategies due to this sector's continuous technological changes.…”
Section: Introductionmentioning
confidence: 99%
“…1 a Fly ash; b silica fume; c GGBS; d rice husk ash; e bagasse ash; and f coconutbased waste ash [5][6][7] agricultural and food wastes as shown in Fig. 3b [17][18][19][20][21]. Various studies have been and are being conducted on the utilization of industrial wastes in concrete production.…”
Section: Introductionmentioning
confidence: 99%
“…2 a Global cement and waste produced; b classification of wastes produced [12][13][14] Fig. 3 a Industrial waste produced; b agricultural and food wastes produced [15][16][17][18][19][20][21] system when it is calcined and uncalcined. The graphical abstract representing the present study carried out for agroindustrial-based wastes used as SCM or AAB materials, and its effect after calcination is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Its main components are the skin and the crushed pulp of the olive; it still contains a certain amount of fat and a large amount of water, which varies according to the variety of olives and especially the extraction process used. The pomace derived from the pressure system contains a moisture content of about 30 % [5]. However, Continuous 3 and 2-phase centrifugal extraction systems, on the other hand, leave a much wetter pomace with a moisture content of between 45 and 65 % [6].…”
Section: Introductionmentioning
confidence: 99%